E6 viral protein ratio correlates with outcomes in human papillomavirus related oropharyngeal cancer. Issue 2 (1st February 2016) - Hong, Angela; Zhang, Xiaoying; Jones, Deanna; Zhang, Mei; Lee, C. Soon; Lyons, J. Guy; Veillard, Anne-Sophie; Rose, Barbara
ABSTRACT: Background: The study aimed to identify prognostic markers to improve the management of patients with HPV positive OSCC Methods: We determined the ratio of HPV E6*I and E6*II splice variants by quantitative RT-PCR in 177 HPV positive OSCC and correlated the findings with other clinicopathological data Results: There was no significant difference in locoregional recurrence (HR 1.72 p = 0.24) and death (HR 1.65, p = 0.13) among patients whose tumors had an E6*I/*II ratio ≥1 compared with an E6*I/*II ratio of <1. Univariate analysis showed that patients with E6*I/*II ≥1 OSCC were more likely to have an event. In the multivariable analysis, there was a trend for more events in patients with E6*I/*II ratio ≥1 (HR 1.70, 95% CI 0.95-3.03, p = 0.07) Conclusion: Our data suggest that the use of HPV 16 spliced transcripts may help to predict for poorer outcomes in patients with HPV positive OSCC.